A model of IS/IT investment and organisational performance in the banking industry sector - Maimbo, Hilangwa; Pervan, Graham (Southern Cross University, 2001)
Information Systems/Information Technology (IS/IT) has now become an integral part of all organisations.Ironically, although there has been a lot of research undertaken in IS/IT strategic planning, little has been doneto understand the actual relationship between IS/IT investment and performance. This study will endeavour toinvestigate this relationship. Given the enormous levels of IS/IT investment that financial institutions have made and continue to make, the results of this study will be of interest to both practioners and academics alike and should assist not only in understanding the value of previous investments, but also in future decision making processes regarding any new investments.